Metaphors and Social Status in Rambu Solo’ Funeral Ceremony - Resnita Dewi; Muhammad Darwis; M. L. Manda; Nurhayati - (Peneliti.net, 2020)
This research is to describe how social status is expressed through metaphors in Rambu Solo’ funeral ceremony. This research is a qualitative descriptive type. Data sourced from the Kada-Kada Tominaa used at the Rambu Solo’ funeral ceremony record techniques, and interview techniques. The results showed that social status in Rambu Solo’ funeral ceremony 'was metaphorious through (1) born of the moon; (2) Born from the Sun; (3) Londong (Rooster); (4) Gayang (Kris); (5) Rar ' (Traditional Necklace)